ナンキョク ニオケル コウセツ ノ サンソ ドウイタイ ソセイ ダイ1カイ ナンキョク キスイケン シンポジウム - 加藤, 喜久雄; カトウ, キクオ; KATO, Kikuo (1979)
P(論文) 南極氷床への水蒸気輸送過程および降雪の生成過程が,降雪の生成温度のみにより決定されていると考えられてきた南極の降雪の酸素同位体組成(δ^<18>)をどのように規制しているのか検討した.降雪の生成温度が同じてあっても,低気圧下て生成した降雪のδ^<18>O値は高気圧下で生成した降雪のδ^<18>値より大きく,降雪のδ^<18>0値け沿岸低気圧によりもたらされる^<18>0に富んだ水蒸気の供給に大きく規制されている.また,降雪のδ^<18>0値は水蒸気源からの距離,すなわち昭和基地から南極海の開水域までの距離にも規制されている.このように降雪のδ^<18>O値が水蒸気輸送過程によっても大きく規制されていることを考慮し降雪のδ^<18>0値と生成温度との関係を取り扱えば,降雪の生成過程に関する理論的考察から自然の現象が考察しうる.さらに,降雪のみδ^<18>0の月平均値と月平均気温との関係からも降雪の生成過程が考察できることが明らかになった. The transportation process of water vapor to the Antarctic ice sheet is one of the most important factors controlling oxygen isotopic composition of precinitation in Antarctica, which was related only to its temperature of formation in the previous studies. The relationship between the oxygen isotopic composition of fallen snow at Syowa Station and the transportation process of water vapor to the Antarctic ice sheet has been investigated in this study. It was found that the oxygen isotopic composition of fallen snow is largely controlled by the supply of ^<18>O-rich water vapor resulting from the approach of a circumpolar cyclone, and is closely related to the distance between the open sea and the sampling station, Taking into consideration the transportation process of water vapor to the Antarctic ice sheet, the correlation between the temperature of formation and the oxygen isotopic composition of fallen snow provides information about the formation process of snow. The correlation between the monthly means of the oxygen isotopic composition of fallen snow and the surface air temperature also provides information about the formation process of snow. departmental bulletin paper